WARALABA (FRANCHISE) DALAM SISTEM HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Mayasari, Riezka Eka (Fakultas Hukum, Universitas Muslim Indonesia, 2018)
Franchise (Franchise) is one type of modern business that provides a promising advantage. This franchise business also has the benefit that plays an important role in improving the development of small business. In terms of packaging The franchise of this franchise business is also a positive value that can be justified according to Islamic law. In Islamic law, franchise with this model is almost similar to the model syirkah mudharabah (profit sharing), but has progressed with the development of the era and there is a combination of other types of shirkah. AbstrakWaralaba (Franchise) adalah salah satu jenis bisnis modern yang memberikan keuntungan yang menjanjikan. Bisnis waralaba ini juga memiliki manfaat yang memainkan peran penting dalam meningkatkan pengembangan bisnis kecil. Dalam hal pengemasan Waralaba bisnis waralaba ini juga merupakan nilai positif yang dapat dibenarkan menurut hukum Islam. Dalam hukum Islam, waralaba dengan model ini hampir mirip dengan model syirkah mudharabah (bagi hasil), tetapi telah berkembang seiring perkembangan zaman dan ada kombinasi jenis syirkah lainnya.